Intramedullary nailing in a tibial shaft fracture distal to a total knee prosthesis with compromised soft tissue condition - Baegyun Kim; Ji Won Lee; Euisun Yoon; Sungho Lee (Trauma Case Reports)
Case: We present a case report on the management and outcome of a periprosthetic tibial shaft fracture treated with intramedullary nailing. The patient, a 78-year-old female, presented with a history of having undergone total knee arthroplasty ten years ago due to osteoarthritis. She sustained a periprosthetic fracture of the tibial shaft with compromised soft tissues surrounding the fracture site following a motor vehicle accident. Plain radiographs revealed a displaced tibial shaft fracture with a flipped large spiral wedge fragment located distal to the total knee prosthesis. Due to the poor soft tissue condition and the risk of complications in wound healing, as well as the desire to avoid prolonged bed rest and immobilization, intramedullary nailing was chosen as the primary treatment modality. Despite the challenging circumstances, the patient achieved satisfactory healing and recovered her pre-injury ambulation status with no significant complications at the six-month follow-up. Conclusion: Managing periprosthetic tibial shaft fractures in the presence of compromised soft tissues presents significant challenges for orthopedic surgeons. In this case, intramedullary nailing proved to be a suitable treatment option, minimizing soft tissue trauma and providing stable fixation to facilitate early mobilization and weight bearing.